Problems of the narrative term in Algerian fictional criticism during the eighties - Abbaci, Abdallah (Journal of Human Sciences, 2021)
The eighties in Algeria witnessed a remarkable activity in the field of fictional criticism, carried out by a group of critics who approached the Algerian fictional text with various approaches, but these criticisms in their entirety were not concerned with the term in its originality and employment, as most of the critics circulated in their books narrative terms not in their correct contexts and away from their modest connotations at their origin.